2011
DOI: 10.1074/jbc.m110.202697
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction of Pregnenolone Sulfate in Insulinoma Cells

Abstract: The neurosteroid pregnenolone sulfate acts on the nervous system by modifying neurotransmission and receptor functions, thus influencing synaptic strength, neuronal survival, and neurogenesis. Here we show that pregnenolone sulfate induces a signaling cascade in insulinoma cells leading to enhanced expression of the zinc finger transcription factor Egr-1 and Egr-1-responsive target genes. Pharmacological and genetic experiments revealed that influx of Ca 2؉ ions via transient receptor potential M3 and voltage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…The connection between an elevated Ca 2C concentration and the activation of the ERK signaling pathway is accomplished by protein kinase C (PKC), most likely PKCa and PKCbII (Benes et al 1999) and the protein kinase Raf (Kolch et al 1993, Corbit et al 2003, Duan & Cobb 2010. Given the similarities between glucose and pregnenolone sulfateinduced signaling, it is not surprising that Raf and ERK are activated in pregnenolone sulfate-stimulated insulinoma cells (Mayer et al 2011 (Mayer et al 2011), suggesting that calcineurin may be part of a second negative feedback loop in the pancreatic b-cells (Fig. 3).…”
Section: Pregnenolone Sulfate: a Ligand For Different Channels And Rementioning
confidence: 99%
See 2 more Smart Citations
“…The connection between an elevated Ca 2C concentration and the activation of the ERK signaling pathway is accomplished by protein kinase C (PKC), most likely PKCa and PKCbII (Benes et al 1999) and the protein kinase Raf (Kolch et al 1993, Corbit et al 2003, Duan & Cobb 2010. Given the similarities between glucose and pregnenolone sulfateinduced signaling, it is not surprising that Raf and ERK are activated in pregnenolone sulfate-stimulated insulinoma cells (Mayer et al 2011 (Mayer et al 2011), suggesting that calcineurin may be part of a second negative feedback loop in the pancreatic b-cells (Fig. 3).…”
Section: Pregnenolone Sulfate: a Ligand For Different Channels And Rementioning
confidence: 99%
“…Recently, the screening of a compound library revealed that citrus fruit flavanones such as naringenin and hesperetin and fabacea secondary metabolites selectively inhibit TRPM3 channel activation (Straub et al 2013). The neurosteroid pregnenolone sulfate, the sulfated form of pregnenolone, has been found to activate TRPM3 channels in insulinoma cells and pancreatic b-cells (Wagner et al 2008, Klose et al 2011, Mayer et al 2011 as well as in other cell types. Stimulation with pregnenolone sulfate also activates TRPM3 channels in HEK293 cells, vascular smooth muscle cells, and synovial fibroblasts (Ciurtin et al 2010, Klose et al 2011, confirming that TRPM3 functions as a Ca 2C -permeable non-selective cation channel.…”
Section: Ligands and Inhibitors Of Trpm3 Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…We discovered that TRPM3 stimulation induces a intracellular signaling cascade that results in the activation of the stimulus-responsive transcription factors AP-1, c-Fos, cJun, CREB, Egr-1, and Elk-1. [1][2][3][4][5] The natural ligands for TRPM3 channels are still unknown, but several compounds have been suggested to function as TRPM3-specific agonists. In most of these studies, the influx of Ca 2C ions into the cells and the subsequent rise in the intracellular Ca 2C concentration was used as an indication of activated TRPM3 channels.…”
Section: Transient Receptor Potential M3 (Trpm3) Is a Camentioning
confidence: 99%
“…The lentiviral transfer vectors pLL.TRPM3, encoding a TRPM3-specific shRNA, has been described. 1,4 The viral particles were produced as previously described 13,14 by triple transfection of 293T/17 cells with the gag-pol-rev packaging plasmid, the env plasmid encoding VSV glycoprotein, and the transfer vector.…”
Section: Lentiviral Gene Transfermentioning
confidence: 99%